An Ethnolinguistic Study of Form and Reference Name of Fish and Seaweed Category - Maria Magdalena Sinta Wardani (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
This qualitative research aims to describe the form and reference in the name of the type of iwak ‘fish’ and karangan 'seaweed' used by the fishing communities of Baron Beach, DIY. Data collection was carried out with literature review, participatory observation, and in-depth interviews. The informants were three fishermen from Kemadang Village, Tanjungsari District, Gunung Kidul Regency, DIY. Unit of analysis is in the form of words related to service activities used in daily life. This study describes lingual units used as type names. The results showed that the names of the types of fish and seaweed categories were basic and derivative forms. Derivative forms include affixed and compound words. Meanwhile, reference to the names of fish and seaweed category types include tools, body parts, animals, plants, shapes, colors, sex, circumstances, professions, and myths.